The Volatility Effect in China - David Blitz; Matthias X. Hanauer; Pim van Vliet (Journal of Asset Management, 2021)
This paper shows that low-risk stocks significantly outperform high-risk stocks in the local China A-share market. The main driver of this low-risk anomaly is volatility, and not beta. A Fama–French style VOL factor is not explained by the Fama–French–Carhart factors, and has the strongest stand-alone performance among all these factors. Our findings are robust across sectors and over time, and consistent with previous empirical evidence for the US and international markets. Moreover, the VOL premium exhibits excellent investability characteristics, as it involves a low turnover and remains strong when applied to only the largest and most liquid stocks. Our results imply that the volatility effect is a highly pervasive phenomenon, and that explanations should be able to account for its presence in highly institutionalized markets, such as the US, but also in the Chinese market where private investors dominate trading.
Keywords: G11; G12; G14; 330; China A shares; Low risk; Low volatility; Low beta; Minimum variance; Anomaly; Value; Size; Momentum; Profitability; Investments; Smart beta; Low-volatility investing